Research progress on NLRP3 inflammasome regulation of periodontitis - LI Xuejing; SU Jiansheng (Kouqiang hemian waike zazhi)
Nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing protein 3 (NLRP3) inflammasome is a multi-protein complex that exists in the cytoplasm. It is involved in innate immune response and can regulate several inflammatory diseases. Periodontal pathogens can stimulate the secretion of several inflammatory cytokines via activating the NLRP3 inflammasome, resulting in periodontal inflammatory disease. This review provides a theoretical overview of periodontal pathogens that are reportedly capable of inflammasome activation, aiming to further exploration of the pathogenesis of chronic periodontitis (CP), which is essential for prevention and developing potential treatment approaches.